2010
DOI: 10.3748/wjg.v16.i23.2895
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal dissection training with pig models in a Western country

Abstract: Training in animal models could help endoscopists overcome the learning curve before starting ESD in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
82
0
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 16 publications
2
82
0
2
Order By: Relevance
“…While training in animal models may not be needed in Japanese institutions where supervision by experts is easily available, these models can be a valuable resource when training in the West. Models could allow endoscopists to ascend the learning curve in a relatively short time, especially when training in low volume centers or/and without direct expert supervision [32,37,63,64] . Two prospective studies were aimed in determining the results, efficacy, and safety of ESD performed in pigs by an endoscopist at the beginning of the learning curve prior to its application in humans.…”
Section: Esd Training In the Westmentioning
confidence: 99%
See 3 more Smart Citations
“…While training in animal models may not be needed in Japanese institutions where supervision by experts is easily available, these models can be a valuable resource when training in the West. Models could allow endoscopists to ascend the learning curve in a relatively short time, especially when training in low volume centers or/and without direct expert supervision [32,37,63,64] . Two prospective studies were aimed in determining the results, efficacy, and safety of ESD performed in pigs by an endoscopist at the beginning of the learning curve prior to its application in humans.…”
Section: Esd Training In the Westmentioning
confidence: 99%
“…The studies showed that training in pigs could be started without such previous learning, and may augment the acquisition of skills in low-volume centers. However, ESD involves maneuvers that traditionally have not been used during flexible endoscopy, which would be difficult to master by oneself [64,65] . The harvested porcine organs are ready-to-use and inexpensive means of becoming proficient in these techniques.…”
Section: Esd Training In the Westmentioning
confidence: 99%
See 2 more Smart Citations
“…The in-vivo pig model has proven to be adequate for endoscopic training in the upper digestive tract [3,4]. Anatomy of the pig´s stomach is quite similar to the human anatomy, even though it has a stronger and protruding Pylorus (Torus Pyloricus) [5].…”
Section: Introductionmentioning
confidence: 99%